Analisa Baterai Sebagai Sumber Kelistrikan Kendaraan Roda Dua Ditinjau Dari Kapasitas Dan Efisiensi - Karimah, Cahyaning Nur; Zain, Alex Taufiqurrohman; Nofiansyah, Acmad Luqman (Jurnal Teknik Terapan, 2023)
This study aims to determine the effect of the comparison of Lithium Iron Phosphate (LiFePO4) batteries with dry and wet batteries as a substitute for batteries in automatic motorcycles. The method used in this study is to compare the efficiency value against each yield value of Lithium Iron Phosphate (LiFePO4) batteries, dry batteries, and wet batteries. The results of this study are when testing the discharge (discharger) and charging (charger) the results of the calculation of the efficiency of Lithium Iron Phosphate (LiFePO4) batteries are 96,02%, dry batteries are 84,76%, and wet batteries are 92,22%.